전통시장 서제 중심의 디스플레이 연구 및 전용서체 개발 - 김초아(Cho-Ah Kim); 장윤정(Yun-Jeong Jang); 김용철(Yong-Chul Kim) (한국콘텐츠학회 논문지, 18(2), 2018)
Traditional market is a place filled with traditional culture and sentiments of the local population, so this is not just a commodity trading places that has been at the centre of our life, including culture and the local economy and the people of the community. However, many consumers still ongoing by the facilities that aging is deprived to the department stores and hyper-marts. Also, low awareness of the displayer, including the internal facilities, is very reality is bad development compared to the appearance, in particular product names, price tags and one mark of origin, such as signs, despite Upon entering the market first leaps to the eye are not improved the situation as it is necessary for the improvement of typography for traditional market. Therefore, examine the fonts used in the traditional markets, proceed to further analysis in the future by building a dedicated font made of only the traditional market it has a distinctive identity and unity of the market typography to present the guidelines of the market font. 전통시장은 지역주민의 전통문화와 정서가 담긴 곳으로 단순히 상품의 거래의 공간이 아닌 문화공간, 지역 경제, 커뮤니티 등 우리 삶의 중심에 있어 왔다. 그러나 시설의 노후화 등으로 대형마트, 백화점등에 소비자를 지속적으로 빼앗기고 있는 실정이다. 내부 시설을 포함 디스플레이에 대한 인식이 낮아 겉모습에 비해 개발이 매우 저조한 실정이며 특히 제품명, 가격표, 원산지 등을 표기한 표지판은 시장 내 들어서면 가장 먼저 눈에 띔에도 불구하고 개선이 되어 있지 않은 실정이며 이러한 전통시장 서체에 대한 개선이 필요한 실정이다. 전통시장 내 사용되는 서체를 조사 분석을 진행해 차후에 더 나아가 전통시장만의 전용 서체를 만들어 시장 서체의 통일성을 갖추고 차별화 된 아이덴티티를 구축하여 전통시장 전용 서체를 개발하고자 한다.